2017
DOI: 10.1111/joa.12617
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic anatomy of the visceral fasciae

Abstract: The term 'visceral fascia' is a general term used to describe the fascia lying immediately beneath the mesothelium of the serosa, together with that immediately surrounding the viscera, but there are many types of visceral fasciae. The aim of this paper was to identify the features they have in common and their specialisations. The visceral fascia of the abdomen (corresponding to the connective tissue lying immediately beneath the mesothelium of the parietal peritoneum), thorax (corresponding to the connective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…The alar fascia is the thinnest and is continuous with the visceral fascia at the level of the oesophagus. It has been reported that visceral fasciae (also called 'investing fasciae' by Stecco et al 2017) are rich in hyaluronic acid and elastic fibres, and they facilitate the sliding and movements of organs. Hyaluronic acid is synthesized by fibroblast-like cells, and the quantity depends on fascial type, regardless of age and sex (Stecco et al 2011(Stecco et al , 2018Fede et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The alar fascia is the thinnest and is continuous with the visceral fascia at the level of the oesophagus. It has been reported that visceral fasciae (also called 'investing fasciae' by Stecco et al 2017) are rich in hyaluronic acid and elastic fibres, and they facilitate the sliding and movements of organs. Hyaluronic acid is synthesized by fibroblast-like cells, and the quantity depends on fascial type, regardless of age and sex (Stecco et al 2011(Stecco et al , 2018Fede et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The esophagus itself is fascially attached to the diaphragm and to the pleurae, not only to allow better movement among different districts but also to preserve its own positional identity. 72 , 73 …”
Section: Introductionmentioning
confidence: 99%
“…Any tension in the myofascial system that affects the orbit is picked up by the periorbita, which is connected with the Tenon's fascia with the epicranial fascia. Constant, excessive tension coming from the limbs can be transferred in the proximal direction as far as to the head, along the connection of the trunk with the platysma muscle and neck extensors [ 69 71 ]. An interesting study was conducted by Ohno-Matsui et al who made an attempt to investigate the structural features of the posterior part of the episclera and the Tenon's fascia in patients with high myopia [ 70 ].…”
Section: Early Intervention and Nonpharmacological Therapy Of Myopmentioning
confidence: 99%